COLLABORATIVE PHENOMENOLOGICAL PRACTICES - COSMESCU, Alexandru (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
In the present paper, I examine the possibility of doing phenomenology in a collaborative manner. Faced with the fading of the ethos of seeing for oneself and the predominance of meta-phenomenology passing for phenomenological work, Herbert Spiegelberg proposed the organization of phenomenology workshops. After offering an analysis of the method of philosophical workshops exemplified by a contemporary proponent of philosophical practice, Oscar Brenifier, I identify several problems such a workshop can face and several commitments that can help create the co-subjectivity necessary for sym-phenomenologizing.